COMBINATION OF RICE HUSK WASTE AND KAPOK SHELL WASTE AS ACTIVE CARBON IN REDUCING LEVELS OF Fe, Mn, pH, TURBIDITY, and TDS IN DUG WELLS IN THE RAWA MAKMUR PERMAI AREA, BENGKULU CITYCOMBINATION OF RICE HUSK WASTE AND KAPOK SHELL WASTE AS ACTIVE CARBON IN REDUCING LEVELS OF Fe, Mn, pH, TURBIDITY, and TDS IN DUG WELLS IN THE RAWA MAKMUR PERMAI AREA, BENGKULU CITY - Riang Adeko; Habibi Hidayat; Andriana Marwanto (Proceeding B-ICON, 2023)
Water is a basic need for life, especially for humans who always need water throughout their lives. Humans use water for daily needs such as drinking, bathing, washing, toileting, and so on. After measurements were carried out, the turbidity results were 113 NTU, pH 9; The iron (Fe) content is 4.83 mg/L, manganese (Mn) is 1.75 mg/L, and TDS is 336 ppm. The aim of this research was to determine the decrease in Fe, Mn, pH, turbidity and TDS levels before and after treatment using varying thickness combinations of rice husks and kapok shells of 20 cm, 30 cm, 50 cm. This type of research uses a quasi-experimental method (Quasi Experimental) with a post test design with control group, namely research carried out before and after treatment. Then the difference between the two measurements is looked for and the difference is considered as a result of the treatment. The research results showed that the reduction in Fe, Mn, pH, turbidity and TDS levels occurred very significantly even though the turbidity and TDS did not meet the quality standards required by Minister of Health Regulation No. 2 of 2023.